Phytochemical Investigation and Anti-angiogenic Examination of Iraqi Vigna radiata L. Seeds and Sprouts - Qassim, Rabab H.; J. Kadhem, Enas (Iraqi Journal of Pharmaceutical Sciences, 2020)
Abstract The objective of this study was to investigate the phytochemical constituents of two different parts of Vigna radiata (seeds and sprouts), and identify their anti angiogenic activity .the goal was achieved by Preliminary qualitative phytochemical screening for crude ethanolic extract of two parts of plant ; rat aorta anti-angiogenesis assay had been conducted for both extracts . isolation , separation and purification of some phytochemical constituents that belong to important groups (flavonoids) from n-butanol fraction extract of Vigna radiata plant had been done in pure form by using preparative thin layer chromatography ( PTLC ) and then subjected to different spectral analytical and physicochemical techniques to identify their chemical structure : melting point ( M. P) , thin layer chromatography ( TLC ) high performance liquid chromatography ( HPLC ) , Fourier transforms infrared spectra ( FTIR ) . and high performance thin layer chromatography ( HPTLC ).the result showed that the existence of coumarin , alkaloids, phenols, flavonoids , terpenoids, phytosterol and saponin.Vitexin and isovitexin were isolated in pure form .n-butanol fraction of sprouts showed highest percentage of blood vessels inhibition ( 88%) in comparison to n-butanol fraction of seeds which showed (56%). There IC50 were 58.8µg/ml and 56.6 µg/ml respectively. The difference of anti angiogenic activity may be related to the variation of concentration of the bioactive constituents or appearance of new bioactive constituents during germination. Keywords: Vigna radiata, vitexin, isovitexin ,high performance thin layer chromatography HPTLC , high performance liquid chromatography HPLC